There is no need to shout to be heard! The paradoxical nature of corporate social responsibility (CSR) reporting in a Latin American family small and medium-sized enterprise (SME). (May 2020) - Discua Cruz, Allan
Drawing on the paradox and reciprocal stewardship theory, this study focuses on tensions in corporate social responsibility (CSR) reporting experienced by a family small and medium-sized enterprise (SME) in a developing Latin American country. Prior literature has suggested a prescriptive, tension-free process, led by family members and driven by an interest to protect and enhance the reputation of both the family and the firm. Relying on an in-depth qualitative approach, this study unveils that CSR reporting is not immune to contradictions between familial and external expectations. The findings reveal that religious beliefs can emerge as a strong source of tensions. A reciprocal stewardship perspective allows an understanding of how and why family and non-family members work together and handle paradoxes. A conceptual model is proposed which is based on multiple sources of emergence (family-related, business-related and external sources) and management/avoidance of tensions in CSR reporting, mediated by the types of relationships among family members and between family and non-family members. Implications and opportunities for further research are subsequently presented.